2002
DOI: 10.1046/j.1467-789x.2002.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive strategies against weight gain and obesity

Abstract: A well-resourced, comprehensive, population-based set of strategies is needed to attenuate and eventually reverse the current trends of increasing obesity prevalence now apparent in most countries. The Epidemiological Triad (host, vector, environment) has proven to be a robust model for other epidemics and is applied to obesity. Host-based strategies are primarily educational and these tend to be most effective among people with higher incomes and higher educational attainment. The main vectors for a high-ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
269
0
12

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(293 citation statements)
references
References 106 publications
4
269
0
12
Order By: Relevance
“…This dearth of population health approaches resulted despite the broad search strategy and inclusion criteria used (see Table 2 and section 3.3 of Flynn et al 2006). Clearly, this synthesis supports the contention of other researchers (Kumanyika, 2001;Swinburn & Egger, 2002) that there is a lack of published and unpublished research and evaluation of population health approaches to address childhood obesity (Flynn et al 2006). A final key component of the synthesis was the development of a 'features table', which outlined the main characteristics for each of the top-ranking 147 programmes according to their settings (school, home, community, clinic etc.…”
Section: Reducing Obesity In Children: a Synthesissupporting
confidence: 61%
“…This dearth of population health approaches resulted despite the broad search strategy and inclusion criteria used (see Table 2 and section 3.3 of Flynn et al 2006). Clearly, this synthesis supports the contention of other researchers (Kumanyika, 2001;Swinburn & Egger, 2002) that there is a lack of published and unpublished research and evaluation of population health approaches to address childhood obesity (Flynn et al 2006). A final key component of the synthesis was the development of a 'features table', which outlined the main characteristics for each of the top-ranking 147 programmes according to their settings (school, home, community, clinic etc.…”
Section: Reducing Obesity In Children: a Synthesissupporting
confidence: 61%
“…An emerging body of literature has suggested environmental factors can influence individuals' dietary behaviour (Giskes, Kamphuis et al 2007). The underlying biological tendency for humans to acquire and store energy and the desensitisation of our appetite control system (Foresight 2007) within the context of an obesogenic environment ('the sum of influences that the surroundings, opportunities, or conditions of life have on promoting obesity in individuals or populations' (Swinburn and Egger 2002)) means individuals exert less control and choice over their lifestyle patterns which impacts on their weight (King and Thomas 2007). It has been suggested that 'human biology has become out of step with the structure of society' (King and Thomas 2007).…”
Section: Research 2007)mentioning
confidence: 99%
“…Health promotion interventions delivered in community settings (compared with hospital settings) have the advantage of being more accessible for socially disadvantaged groups (18) . Although some studies have shown some promising results, the evidence base for community-based obesity prevention interventions is currently limited and inconclusive (19,20) . The present study aimed to assess the effectiveness of a brief face-to-face health promotion intervention using brief negotiation techniques (intervention locations) compared with standard advice-giving techniques (control locations), delivered in a community setting, to promote healthy diets and levels of physical activity in adults living in low socio-economic areas of Middlesbrough (UK).…”
mentioning
confidence: 99%